P123 The effect of necrosis inhibition on acute DSS colitis model of inflammatory bowel disease. (16th January 2018) - Lee, D; Koo, J S; Kim, C H; Hwang, S H; Choe, J W; Kim, S Y; Jung, S W; Yim, H J; Jeen, Y T; Lee, S W
Abstract: Background: Inflammatory bowel diseases (IBD) were characterised by uncontrolled chronic inflammation, which lead to cell death and organ damage. In contrast to apoptotic cell death, necrosis is characterised by destruction of cell membrane, which released substances from the cells causing the inflammatory reaction and a cascade of vicious inflammatory cycle resulting in increased necrosis. Although necrosis is thought be a main cell death mechanism of IBD, few attempts have been made to reduce necrosis in IBD. A novel necrosis inhibitor (NI, NecroX-7) is recently developed, which blocks the opening of mitochondrial permeability transition pore and inhibits necrosis effectively. The aim of this study investigated the effect of necrosis inhibition in acute murine colitis model and in-vitro study. Methods: Cleaved PARP-1 fragment band was analysed using western blot assay in intestinal epithelial cell line (IEC-18, rat) in order to confirm the necrosis inhibition effect of NI. And acute dextran-sodium sulfate (DSS) induced colitis was generated in C57BL/6 mice. NI (30 mg/kg) was administered once a day via oral gavage for 8 days from the day before DSS administration. The severity of colitis was assessed by weight, colon length and histologic score. And HMGB1 immunochemistry was performed on harvested intestine for evaluating necrotic cell death qualitatively. The inflammatory cytokines mRNA expressions were measured by quantitative RT-PCR. Results: In the necrosis inhibition group, the expression of cleaved PARP-1 (55kDa, necrosis marker) was reduced compared with the control group, whereas the cleaved PARP-1 fragment (89 kDa, apoptosis marker) was not different between groups. In vivo study, NI treatment significantly reduced colitis represented by colon length and histologic score. HMGB-1 expression was also significantly reduced in NI group. In addition, the expression of inflammatory cytokines was reduced in NI group, especially, interlukin-1 β was significantly lower. Conclusions: A necrosis inhibition effectively reduced DSS induced colitis and inflammatory cytokines. Necrosis inhibition might be a new approach to treat inflammatory bowel disease.